The Effect of Foot Reflection Massage on Hypertension in Elderly Batam City - Roza Erda; Fitria Tamara; Trisya Yona; Didi Yunaspi (Indonesian Journal of Global Health Research, 2020)
The results of the report on the health recording system for the elderly in Batam City in 2018 with the most hypertension sufferers are in the Sei Langkai Health Center area with a total of 4,863 people. This study was to determine whether there was an effect of foot reflexology therapy in the elderly with The type of design in this study was the Quasi Experimental method using the Onegroup Pretest-Postest Design. The sample used in this study amounted to 15 elderly people who have hypertension. The sampling technique used purposive sampling. This research was conducted on 20 June August 2020 in the Sei Langkai Community Health Center, Batam City. The research results were analyzed using paired t-test. The result showed that the systolic and diastolic blood pressure pre test and post test obtained a value of 0.000 (<0,05) based on this it can be concluded that there is a significant effect on Foot Reflexology on reducing blood pressure in the elderly. It is hoped that the elderly can maintain a healthy lifestyle and do light exercise to avoid an increase in blood pressure.